Key-competences in higher education as a tool for democracy - Raffaella Rumiati; Alberto Ciolfi; Annalisa Di Benedetto; Morena Sabella; Maria Rita Infurna; Alessio Ancaiani; Daniele Checchi (Firenze University Press, 2018)
As the focus of teaching progressively moves from being merely transmissive to being student-centred, under the beneficial pressure of the European recommendations, the debate on how to form and measure competences in students has become topical. This transformation was made necessary to nudge education institutions towards accountability, and to allow students (and their families) to make informed school choices. Large-scale achievement or cognitive tests were then developed by international organizations and administered in schools. The focus of the present paper is to provide empirical evidence that this process can be successfully embraced also by the higher education system. To this end we report data from several surveys in which ANVUR, the Italian public agency for the evaluation of universities and research institutes, administered the Test of Competence (TECO) to evaluate generic and disciplinary competences in first- and third-year undergraduate students. Using the value-added approach, we demonstrate that both types of competences can be formed by higher education institutions and that the university attendance makes a difference, especially for the disciplinary competences. The study qualifies TECO as a reliable tool for self-assessment of teaching effectiveness, to be used for evidence-based policies in higher education.   Le competenze-chiave nella formazione universitaria come strumento di democrazia  Mentre l'obiettivo dell'insegnamento passa progressivamente dall'essere semplicemente trasmissivo all'essere centrato sullo studente, grazie anche alla pressione delle raccomandazioni europee, il dibattito su come formare e misurare le competenze negli studenti è andato intensificandosi. Questa trasformazione si è resa necessaria per spingere le istituzioni scolastiche verso una maggiore responsabilità del proprio operato e per permettere agli studenti (e alle loro famiglie) di fare scelte informate. Sono stati pertanto sviluppati dei test cognitivi su larga scala da organizzazioni internazionali, che sono stati poi somministrati nelle scuole. Il punto centrale del presente lavoro consiste nel fornire prove empiriche che questo processo può essere adottato con successo anche dal sistema universitario. A tal fine, riportiamo i dati di diverse sperimentazioni in cui ANVUR, l'agenzia pubblica italiana responsabile della valutazione delle università e degli istituti di ricerca, ha somministrato il Test di Competenze (TECO) per valutare le competenze generiche e disciplinari negli studenti universitari del primo e del terzo anno. Utilizzando l'approccio del valore aggiunto, siamo in grado di dimostrare che l'università può formare entrambi i tipi di competenze e che la frequenza universitaria può fare la differenza, in particolare per le competenze disciplinari. Lo studio qualifica TECO come uno strumento affidabile per l'autovalutazione dell'efficacia dell'insegnamento e può informare scientificamente le politiche universitarie.